Negative pole piece, preparation method thereof and lithium ion battery

Through multi-string coating and dissolving agent treatment, the grooves are constructed in lithium-ion batteries, which solves the lithium-ion problem of graphite negative electrode materials during fast charging, improves the fast charging performance and safety of the battery, and avoids the powder after laser etching Residual problems.

CN119252867APending Publication Date: 2025-01-03ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327242.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The graphite negative electrode material has lithium extraction under fast charging, which leads to the growth of lithium dendrites, which may pierce the separator and cause a short circuit inside the battery. The negative electrode powder after laser etching cannot be effectively removed, affecting battery safety and storage.

Method used

Multi-stripe coating method introduces polymer slurry on the surface of the negative electrode slurry layer to form an interlaced composite layer, and dissolves the precoat layer into grooves through dissolving agents to build additional lithium ion transport channels to avoid polymers. Remaining.

Benefits of technology

It significantly improves the fast charging performance of graphite negative electrode sheet, reduces the safety risks inside the battery, avoids self-discharge and bulging, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252867A_ABST
    Figure CN119252867A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a negative pole piece, a preparation method thereof and a lithium ion battery, and the preparation method comprises the following steps: coating the surface of a current collector with negative slurry, and curing to form an active layer; coating the surface of the active layer with negative electrode slurry and polymer slurry to obtain a composite layer; in the composite layer, the negative electrode slurry and the polymer slurry are obtained by multi-stripe coating; the polymer slurry forms a pre-coating layer, and gaps of the pre-coating layer are filled with the negative electrode slurry; pressing the coated current collector into a sheet, and immersing the sheet into a dissolving agent to dissolve the pre-coating layer and form a groove in the composite layer to obtain a negative pole piece; the polymer slurry layer on the negative pole piece is dissolved in the dissolving agent without residue, and is thoroughly removed before the pole piece is made into a battery, so that the thickness of a battery cell in a finished battery is not influenced; no negative electrode powder or polymer residues exist in the lithium ion battery prepared from the negative electrode plate, the rate charging capacity of the lithium ion battery can be further improved, and the safety risk is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and relates to a negative electrode plate and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Graphite negative electrode material is the most widely used negative electrode material in the lithium-ion battery market. However, graphite negative electrode material has lithium precipitation under fast charging conditions. The precipitated lithium cannot participate in the electrochemical reaction and will grow in the form of dendrites. The lithium dendrites may pierce the diaphragm and cause an internal short circuit in the battery. The precipitated lithium is also prone to form dead lithium, which will not only cause battery capacity decay and shorten life, but also increase safety risks. In addition, the slower lithium insertion process and surface lithium repellency of graphite also limit the fast charging application of lithium-ion batteries.

[0003] In order to improve the fast charging performance of graphite negative electrode materials, the industry currently uses laser to etch grooves with uniform spacing on the surface of the negative electrode plate, uses this groove to widen the spacing between the graphite layers, and constructs additional ion transmission channels to achieve the fast charging needs of lithium batteries; however, in this method, the negative electrode powder left after the laser etching process cannot be effectively removed; after being made into a finished battery, the negative electrode powder will cause a tiny self-discharge inside the battery, which is not conducive to the long-term storage of the battery, and once the self-discharge is too fast, it will also cause the battery to bulge, posing a safety risk. Summary of the invention

[0004] In view of the above problems existing in the prior art, the object of the present invention is to provide a negative electrode plate and a preparation method thereof and a lithium ion battery.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a negative electrode sheet, comprising the following steps:

[0007] Applying negative electrode slurry on the surface of current collector and curing it to form an active layer;

[0008] Coating negative electrode slurry and polymer slurry on the surface of the active layer and curing to obtain a composite layer;

[0009] In the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a pre-coating layer, and the negative electrode slurry fills the gaps in the pre-coating layer;

[0010] The coated current collector is pressed into a sheet and immersed in a solvent to dissolve the pre-coating layer and form a groove in the composite layer to obtain a negative electrode sheet.

[0011] In some embodiments, the step of coating the negative electrode slurry and the polymer slurry on the surface of the active layer to obtain a composite layer comprises:

[0012] The polymer slurry is coated on the surface of the active layer in a multi-striped coating manner and cured to form a pre-coating layer;

[0013] Applying negative electrode slurry in the gaps of the pre-coat layer to fill and solidify to obtain the composite layer;

[0014] or;

[0015] Coating the negative electrode slurry on the surface of the active layer in a multi-striped coating manner and curing the negative electrode slurry layer;

[0016] Applying the polymer slurry in the gaps of the negative electrode slurry layer to fill and solidify to obtain the composite layer;

[0017] or;

[0018] The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head at the same time and then cured to obtain the composite layer.

[0019] In some embodiments, the step of coating the polymer slurry on the surface of the active layer by multi-striped coating and curing to form a pre-coating layer comprises:

[0020] Use multi-strip coating method, with coating spacing of 0.5mm to 3mm, and / or 0.01mm 2 ~0.1mm 2 The polymer slurry is coated on the surface of the active layer and cured to form the pre-coating layer.

[0021] In some embodiments, the thickness of the pre-coating layer is 1 / 4 to 3 / 4 of the total thickness of the coating layer of the negative electrode plate.

[0022] In some embodiments, the polymer used in the polymer slurry is any one of polyamide, polyester, and polyether; and the polymer used in the polymer has a molecular weight of 10,000 to 50,000, and / or a melting point of 50° C. to 80° C.

[0023] In some embodiments, the dissolving agent is any one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, alcohols, and benzene.

[0024] In some embodiments, the mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml.

[0025] In some embodiments, the step of pressing the coated current collector into a dissolving agent to dissolve the pre-coating layer and form a groove on the composite layer to obtain a negative electrode sheet includes:

[0026] Roll-pressing the current collector, and then immersing the current collector in the solvent at 40° C. to 50° C. for 1 to 5 minutes to dissolve the pre-coating layer and form a groove on the composite layer;

[0027] Preferably, after the grooves are formed on the composite layer, the current collector is immersed in N-methylpyrrolidone solvent for 30 to 60 seconds to obtain the negative electrode plate.

[0028] In some embodiments, the curing method is UV curing or drying curing;

[0029] During the UV curing, the intensity of the UV light is 900 mW / cm 2 ~1100mW / cm 2 , and / or the curing power is 30% to 50%, and / or the curing time is 5 to 15 seconds;

[0030] During the drying and curing, the current collector is dried in an oven at 40° C. to 50° C.

[0031] The present invention also provides a negative electrode sheet, which is prepared by the negative electrode sheet preparation method.

[0032] In some embodiments, in the negative electrode plate, the active material of the negative electrode slurry layer is at least one of graphite, hard carbon, soft carbon, silicon-based materials, titanium-based materials, nitrides, tin compounds, metallic lithium, silicon-doped graphite, and lithium titanate.

[0033] The present invention further provides a lithium-ion battery, comprising the above-mentioned negative electrode plate.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] In the present invention, a polymer is introduced on the surface of the negative electrode slurry layer by stripe coating; stripe coating can coat multiple polymer slurry layers at the same time, and a gap is left between each two adjacent polymer slurry layers; the negative electrode slurry is coated in the gap to fill it, so that a composite layer in which the negative electrode slurry and the polymer slurry are arranged alternately can be obtained; the physical miscibility between the solvent and the polymer slurry can be used to make the pre-coating layer completely dissolved in the solvent, so as to construct multiple grooves extending along the length direction of the negative electrode sheet in the composite layer; the range of the polymer slurry layer coating is the negative electrode sheet. The range of groove distribution in the electrode slurry layer; these grooves provide additional transmission channels for lithium ions, which can significantly improve the fast charging performance of the graphite negative electrode plate; the polymer slurry layer on the negative electrode plate is completely dissolved in the solvent without residue, and can be completely removed before the negative electrode plate is made into a battery, and will not affect the thickness of the battery cell in the finished battery; compared with the conventional laser etching method in which the negative electrode powder is left inside the battery to generate self-generation, the lithium-ion battery made from the negative electrode plate in the present invention will not have any negative electrode powder or polymer residue inside, effectively reducing the safety risk. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the cross-sectional structure of the coating layer of the negative electrode plate of the present invention;

[0037] In the figure: 10, current collector; 20, active layer; 30, composite layer; 301, pre-coating layer. DETAILED DESCRIPTION

[0038] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0039] See also Figure 1 , Figure 1 Schematic diagram of the cross-sectional structure of the coating layer of the negative electrode sheet of the present invention; the preparation method of the negative electrode sheet comprises the following steps:

[0040] The negative electrode slurry is coated on the surface of the current collector 10 and cured to form an active layer 20;

[0041] A negative electrode slurry and a polymer slurry are coated on the surface of the active layer and cured to obtain a composite layer 30;

[0042] In the composite layer 30, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a pre-coating layer 301, and the negative electrode slurry fills the gaps in the pre-coating layer 301;

[0043] The coated current collector 10 is pressed into a sheet and then immersed in a solvent to dissolve the pre-coating layer 301 and form a groove in the composite layer 30 to obtain a negative electrode sheet.

[0044] Furthermore, the step of coating the negative electrode slurry and the polymer slurry on the surface of the active layer to obtain the composite layer 30 includes:

[0045] The polymer slurry is coated on the surface of the active layer 20 by a multi-striped coating method and cured to form a pre-coating layer 301;

[0046] The gaps of the pre-coating layer 301 are filled with negative electrode slurry and cured to obtain a composite layer 30;

[0047] or;

[0048] The negative electrode slurry is coated on the surface of the active layer 20 by a multi-striped coating method and cured to obtain a negative electrode slurry layer;

[0049] The gaps in the negative electrode slurry layer are filled with a polymer slurry and then cured to obtain a composite layer 30;

[0050] or;

[0051] The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head and then cured to obtain a composite layer 30 .

[0052] The coating of the composite layer 30 in the present invention includes three schemes, namely: first coating the polymer slurry and then coating the negative electrode slurry, or first coating the negative electrode slurry and then coating the polymer slurry, or coating the polymer slurry and the negative electrode slurry at the same time; among them, the scheme of first coating the polymer slurry and curing it, and then coating the negative electrode slurry and curing it is the best; because under such operation, the integrity of the pre-coating layer 301 formed by the polymer slurry can be guaranteed as much as possible, and the possibility of the negative electrode slurry and the polymer slurry flowing with each other during coating and causing the interface between the two to be blurred is greatly reduced; each time after coating the polymer slurry or the negative electrode slurry, a curing step must be performed to avoid the mixing of the negative electrode slurry and the polymer slurry during subsequent coating.

[0053] Furthermore, when the polymer slurry is coated along the length direction of the current collector 10 by multi-strip coating, the coating width of each transversely arranged polymer slurry layer is equal, and an equal-width gap is left between each two adjacent polymer slurry layers; wherein the coating width is 0.5 mm to 3 mm, and / or the coating cross-sectional area is 0.01 mm 2 ~0.1mm 2 ; The length and width of the polymer slurry layer coating are the length and width of the grooves subsequently constructed in the negative electrode slurry layer; these grooves are arranged neatly and orderly, providing additional transmission channels for lithium ions, which can shorten the migration path of lithium ions in the negative electrode, improve ion conductivity, and effectively improve the fast charging performance of the graphite negative electrode sheet, so that the obtained battery has high-rate current charging and discharging performance.

[0054] Furthermore, the thickness of the pre-coating layer 301 is 1 / 4 to 3 / 4 of the total thickness of the coating layer of the negative electrode plate; in this solution, there is no need to increase the total thickness of the coating layer. In the prepared negative electrode plate, the coating layer includes an active layer 20 and a composite layer 30 arranged from the inside to the outside.

[0055] Furthermore, the polymer used in the polymer slurry is any one of polyamide, polyester and polyether; and the polymer used in the polymer has a molecular weight of 10,000 to 50,000, and / or a melting point of 50° C. to 80° C.

[0056] Furthermore, the solvent is any one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, alcohols, and benzene; by utilizing the physical solubility of the polymer in the polymer slurry and the solvent, and then controlling the mass concentration and dissolution time of the polymer slurry, the polymer slurry can be completely dissolved in the solvent, and will not remain on the negative electrode sheet, nor will it have a negative impact on the working performance of the finished battery.

[0057] Furthermore, the mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml; the selection of the mass concentration of the polymer slurry is crucial. If the mass concentration is too low, it will affect the coating effect and curing degree of the polymer slurry, and if the mass concentration is too high, the slurry will have poor fluidity; selecting a polymer slurry with a mass concentration of 10 mg / ml to 50 mg / ml can achieve better coating and curing effects of the polymer slurry while ensuring fluidity.

[0058] Further, the current collector 10 is roll-pressed, and then immersed in a solvent at 40 to 50° C. for 1 to 5 minutes to dissolve the pre-coating layer 301 and form a groove on the composite layer 30; the current collector is immersed in N-methylpyrrolidone solvent for 30 to 60 seconds to obtain a negative electrode sheet; the negative electrode sheet is immersed in the solvent for 1 to 5 minutes to allow the pre-coating layer to be fully dissolved in the solvent, and then immersed in N-methylpyrrolidone solvent to wash away the solvent and polymer that may remain on the negative electrode sheet.

[0059] Furthermore, the curing method is ultraviolet light curing or drying curing;

[0060] During UV curing, the intensity of UV light is 900mW / cm 2 ~1100mW / cm 2 , and / or the curing power is 30% to 50%, and / or the curing time is 5 to 15 seconds;

[0061] During drying and curing, the current collector is dried in an oven at 40°C to 50°C;

[0062] Preferably, the polymer slurry is cured by ultraviolet light, and the negative electrode slurry is cured by drying; this is because the polymer slurry is easier to shape when cured by ultraviolet light, and the time required for the negative electrode slurry to be completely cured by drying is shorter than the time required by ultraviolet light.

[0063] Example 1

[0064] This embodiment 1 provides a negative electrode plate and a lithium-ion battery including the negative electrode plate, wherein:

[0065] 1. Preparation of negative electrode sheet:

[0066] Graphite, carboxymethyl cellulose and polystyrene acrylate are uniformly mixed in a mass ratio of 97.7:1.1:1.2 to prepare a negative electrode slurry;

[0067] Prepare 20 mg / ml polyamide (PA) slurry;

[0068] A layer of negative electrode slurry is coated on the surface of the copper foil, and then dried in an oven at 45° C. to obtain a first active layer on the surface of the copper foil;

[0069] On the surface of the first active layer, stripe coating was used at an interval of 1.5 mm to coat a cross-sectional area of ​​0.02 mm. 2 PA slurry, UV light curing, UV light intensity is 1000mW / cm 2 , the curing power is 40%, the curing time is 10s, and a pre-coating layer is obtained on the surface of the first active layer; wherein the coating thickness of the pre-coating layer is equal to the coating thickness of the first active layer;

[0070] The negative electrode slurry is coated on the blank stripe area of ​​the pre-coating layer, i.e., the gap of the pre-coating layer to fill it, and dried at 60° C. to obtain a second active layer; the second active layer and the pre-coating layer form a composite layer; wherein the coating thickness of the second active layer is equal to the coating thickness of the pre-coating layer and the first active layer, the coating width of the second active layer is equal to the gap width of the pre-coating layer, and the second active layer does not cover the pre-coating layer;

[0071] The coated negative electrode sheet is cold pressed, and then immersed in a 45°C N,N-dimethylformamide (DMF) solvent for 5 minutes to dissolve the PA slurry layer in the DMF solvent. After the PA slurry layer, i.e., the pre-coating layer, is dissolved, a groove is formed on the composite layer;

[0072] After the PA slurry layer on the negative electrode sheet is completely dissolved, immerse the negative electrode sheet in N-Methylpyrrolidone (NMP) solvent for 1 minute, and use NMP to clean and remove the residual polymer on the surface of the negative electrode sheet; take out the negative electrode sheet, cut it into strips and keep it for later use.

[0073] 2. Preparation of positive electrode sheet:

[0074] The lithium iron phosphate, the conductive agent and the binder are uniformly mixed in a mass ratio of 97:1.5:1.5 to prepare a positive electrode slurry; wherein the conductive agent is conductive carbon black and the binder is polyvinylidene difluoride (PVDF);

[0075] The positive electrode slurry is coated on aluminum foil, dried at 85°C, and then cold pressed, cut into strips, and stored for later use.

[0076] 3. Preparation of diaphragm:

[0077] The PE-based film is coated with aluminum oxide / PVDF slurry on both sides, and after drying, it is cut into strips and kept for later use.

[0078] 4. Preparation of electrolyte:

[0079] Lithium hexafluorophosphate (LiPF6) is dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) to obtain an electrolyte with a concentration of 1 mol / L; the mass ratio of EC, DMC and EMC in the mixed solvent is 1:2:1.

[0080] 5. Preparation of lithium-ion batteries:

[0081] The negative electrode sheet, positive electrode sheet, separator and electrolyte obtained in the above steps are combined to prepare a soft-pack lithium-ion battery, which is left to stand at room temperature for 24 hours and at high temperature for 16 hours before use.

[0082] Example 2-3

[0083] Specifically, embodiments 2-3 all provide a negative electrode sheet and a lithium-ion battery including the negative electrode sheet;

[0084] The only difference between Example 2 and Example 1 is that the coating spacing of the PA slurry is 0.5 mm;

[0085] The only difference between Example 3 and Example 1 is that the coating interval of the PA slurry is 3 mm.

[0086] Embodiment 4-5

[0087] Specifically, embodiments 4-5 all provide a negative electrode sheet and a lithium ion battery including the negative electrode sheet;

[0088] The only difference between Example 4 and Example 1 is that the coating cross-sectional area of ​​the PA slurry is 0.01 mm 2 ;

[0089] The only difference between Example 5 and Example 1 is that the coating cross-sectional area of ​​the PA slurry is 0.06 mm 2 .

[0090] Embodiment 6-7

[0091] Specifically, embodiments 6-7 all provide a negative electrode sheet and a lithium ion battery including the negative electrode sheet;

[0092] The difference between Example 6 and Example 1 is that when coating the composite layer, the negative electrode slurry is coated first, and then the polymer slurry is coated, wherein the cross-sectional area of ​​the polymer coating is 0.02mm 2 , coating spacing 1.5mm;

[0093] The only difference between Example 7 and Example 1 is that when coating the composite layer, a dual die head is used to simultaneously coat the polymer slurry and the negative electrode slurry, wherein the cross-sectional area of ​​the polymer coating is 0.02 mm 2 , coating spacing 1.5mm.

[0094] Example 8

[0095] Embodiment 8 provides a negative electrode sheet and a lithium ion battery including the negative electrode sheet;

[0096] The only difference between Example 8 and Example 1 is that the DMF solvent is replaced by ethanol.

[0097] Comparative Example 1

[0098] This comparative example 1 provides a negative electrode sheet and a lithium ion battery including the negative electrode sheet. Specifically, the difference between comparative example 1 and embodiment 1 is that:

[0099] After coating the negative electrode slurry on the surface of the copper foil to obtain the first active layer, a layer of negative electrode slurry is coated on the surface of the first active layer, and then dried at 60° C. after coating to obtain the second active layer; the negative electrode sheet is cold pressed and reserved for use; wherein the coating thickness of the first active layer and the second active layer are the same as the coating thickness of the first active layer and the second active layer in Example 1;

[0100] The negative electrode plate in this comparative example 1 is only coated with the negative electrode slurry, and is not coated with the PA slurry; meanwhile, the negative electrode plate is not subjected to the treatment steps such as DMF solvent immersion and NMP solvent washing.

[0101] Comparative Example 2

[0102] This comparative example 2 provides a negative electrode plate and a lithium ion battery including the negative electrode plate. Specifically, the difference between comparative example 2 and example 1 is only that:

[0103] In this comparative example 2, a layer of negative electrode slurry is coated on the surface of the copper foil and then dried at 60° C. The coating thickness of the negative electrode slurry is equal to the total thickness of the negative electrode sheet coating layer in Example 1;

[0104] A plurality of grooves with a width of 1 mm and arranged along the length direction of the electrode are punched on the surface of the slurry layer by laser etching, and the spacing between each two adjacent grooves is 1.5 mm;

[0105] The negative electrode sheet is cold pressed and stripped and then kept for later use;

[0106] As a control, in Comparative Example 2, a laser etching method was used to construct a groove of the same size as that in Example 1.

[0107] Comparative Example 3

[0108] This comparative example 3 provides a negative electrode sheet and a lithium ion battery including the negative electrode sheet. Specifically, the difference between comparative example 3 and embodiment 1 is only that:

[0109] In this comparative example 3, the 20 mg / ml PA slurry prepared in Example 1 and the negative electrode slurry are mixed in a mass ratio of 1:1 to obtain a mixed slurry. A layer of the mixed slurry is coated on the surface of the copper foil and then dried at 60°C. The dried negative electrode sheet is cold pressed and stripped, and retained for later use; wherein the coating thickness of the mixed slurry is equal to the total thickness of the negative electrode sheet coating layer in Example 1.

[0110] Comparative Examples 4-5

[0111] Specifically, Comparative Examples 4 and 5 both provide a negative electrode sheet and a lithium-ion battery comprising the negative electrode sheet;

[0112] The difference between Comparative Example 4 and Example 1 is that the coating spacing of the PA slurry is 0.1 mm;

[0113] The only difference between Comparative Example 5 and Example 1 is that the coating spacing of the PA slurry is 5 mm.

[0114] Test Case

[0115] The lithium ion batteries obtained in Examples 1-8 and Comparative Examples 1-5 were subjected to the following operations:

[0116] Cyclic capacity test: In the voltage range of 2.5-4.2V, the battery test system of Newwell Electronics Co., Ltd. was used to perform charge and discharge tests on various lithium-ion battery samples at rates of 0.2C, 0.5C, 1C, 3C, and 5C. The test results are shown in Table 2. The test also included 600 charge and discharge cycles at a constant current density of 3C. The test results are shown in Table 1.

[0117] Table 1. Specific capacity test results of 600 cycles at 3C rate

[0118]

[0119]

[0120] Table 2. Cycle specific capacity test results at different rates

[0121] sample 0.2C 0.5C 1C 3C 5C Example 1 158.1 142.4 124.7 113.7 107.9 Comparative Example 1 149.7 138.2 118.6 93.7 83.2 Comparative Example 2 153.7 139.6 119.4 99.7 73.4

[0122] K value test: first let the lithium-ion battery stand at 45°C for 24 hours, then let it stand at room temperature for 48 hours; after standing, test the first voltage U1;

[0123] Then let the lithium-ion battery stand at room temperature for 48 hours; after standing still, test the voltage U2 for the second time;

[0124] The K value is calculated based on the two voltage drops, K = (U2-U1) / T; the test results are shown in Table 3.

[0125] Table 3. K value defect rate test results

[0126]

[0127] Battery impedance test: The conventional method was used to perform impedance test on the batteries prepared in the examples and comparative examples. The test results are shown in Table 4.

[0128] Table 4. Battery impedance test results

[0129]

[0130]

[0131] By observing the test results of Example 1 and Comparative Example 1 in Table 1, Table 2 and Table 4, it can be seen that after 600 cycles at a 3C rate, the discharge specific capacity of the lithium ion battery in Example 1 is 101.5 mAh / g, which is 39.6 mAh / g higher than the discharge specific capacity of the lithium ion battery in Comparative Example 1; the cycle specific capacity of the lithium ion battery in Example 1 at different rates is also much higher than the cycle specific capacity of the lithium ion battery in Comparative Example 1; in addition, compared with Comparative Example 1, the battery impedance of the lithium ion battery in Example 1 is 3.5 mΩ smaller; compared with the negative electrode sheet coated with only the negative electrode slurry in Comparative Example 1, in Example 1, grooves can be constructed on the surface of the composite layer of the negative electrode sheet by physical dissolution of PA by DMF solvent, providing additional ion transmission channels for lithium ions, effectively improving the ion transmission capacity at the negative electrode, reducing the battery impedance, and thus improving the cycle performance and charging rate of the battery.

[0132] In addition, by observing the test results of Examples 1 and 6-7 in Tables 1, 2 and 4, it can be seen that the scheme of first coating the polymer slurry, quickly curing it with ultraviolet light, and then coating the negative electrode slurry has obvious advantages. This is because under such an operation, the integrity of the pre-coating layer 301 formed by the polymer slurry can be guaranteed as much as possible, and the possibility of the negative electrode slurry and the polymer slurry flowing with each other during coating and causing the interface between the two to be blurred is greatly reduced; in the schemes of Examples 6 and 7, there may be the possibility that the negative electrode slurry and the polymer slurry flow with each other during coating and cause the interface between the two to be blurred, thereby resulting in a decrease in the performance of the prepared battery.

[0133] By observing the test results of Example 1 and Example 8 in Table 1, Table 2 and Table 4, it can be seen that when the solvent for dissolving the coated polymer is replaced with ethanol, the performance of the lithium-ion battery decreases. This is because DMF has a stronger ability to dissolve polyamide than ethanol under the same conditions. DMF is a highly polar solvent. According to the principle of like dissolves like, polyamide molecules are more likely to enter between DMF molecules at high temperatures, thereby accelerating the dissolution process. In Example 8, since ethanol does not completely dissolve the polyamide, polymer residues will remain in the formed grooves, resulting in a decrease in the performance of the lithium-ion battery.

[0134] Secondly, it can be seen from the test results of Examples 1 to 3, Comparative Example 1, Comparative Example 4 and Comparative Example 5 in Table 1 and Table 4 that when the coating spacing of the polymer slurry is too large or too small, the diffusion resistance of lithium ions will increase, which is not conducive to the improvement of the fast charging performance of the battery; specifically, when the coating spacing of the PA slurry in the stripe coating is too narrow, it will not only cause certain challenges to the coating process, but also easily cause the two adjacent polymer slurries to contact or even overlap, thereby affecting the subsequent coating and rolling effects, resulting in a decrease in the performance of the lithium ion battery; in addition, the shape, depth or spacing of the constructed grooves do not meet the requirements and cannot play a role in accelerating ion transmission; and when the coating spacing of the PA slurry in the stripe coating is too wide, the number of ion channels constructed on the pole piece is insufficient, and the density of the negative pole piece slurry layer is insufficient, which will also lead to a decrease in the cycle performance of the lithium ion battery; in the present invention, when the coating spacing of the polymer slurry is controlled within the range of 0.5 mm to 3 mm, it can not only ensure that the stripe coating work is completed smoothly, but also allow the grooves constructed by the subsequent dissolution of the pre-coating layer to meet the expected effect.

[0135] In addition, it can be seen from the test results of Examples 1, 4 and 5 in Tables 1 and 4 that when the coating cross-sectional area of ​​the PA slurry in the stripe coating is too large or too small, it will also have a certain impact on the impedance and discharge specific capacity of the lithium-ion battery; in the present invention, the coating cross-sectional area of ​​the polymer slurry is controlled to be 0.01 to 0.1 mm 2 Within the range of , the fast charging performance of lithium-ion batteries can be improved to a greater extent.

[0136] Furthermore, after the polymer slurry and the negative electrode slurry of equal mass are mixed and coated on the current collector to obtain a mixed slurry layer, since the organic solvent used in the electrolyte has a certain miscibility with the polymer slurry, the polymer slurry will construct irregularly shaped channels in the mixed slurry layer after being dissolved in the electrolyte; observing the test results of Example 1, Comparative Example 1 and Comparative Example 3 in Table 1 and Table 4, it can be seen that the irregular channels constructed in the mixed slurry layer can indeed reduce the diffusion resistance of lithium ions to a certain extent, but the effect on improving the rate charging of lithium ion batteries is not obvious.

[0137] By observing the test results of Example 1 and Comparative Example 2 in Table 3, it can be seen that the graphite material debris generated by laser etching in Comparative Example 2 cannot be effectively removed during the preparation process of the negative electrode plate. After the negative electrode plate is made into a lithium-ion battery, the self-discharge index inside the battery will increase; the lithium-ion battery test K value mean of Comparative Example 2 is 0.0478mv / h, and the defective rate is 9.87%, which cannot meet market requirements; while the lithium-ion battery of Example 1 does not have this problem, and the K value mean obtained by the test is only 0.03413mv / h, and the defective rate is controlled within <0.1%; it is easy to know that the present invention dissolves the polymer slurry layer in the negative electrode plate by a solvent to construct a groove to provide a transmission channel for lithium ions. Compared with the traditional laser etching method, it can not only further improve the rate charging capacity of the lithium-ion battery, but also improve the safety of the battery and reduce the defective rate.

[0138] The above are only partial or preferred embodiments of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode sheet, characterized in that: The steps include: Applying negative electrode slurry on the surface of current collector and curing it to form an active layer; Coating negative electrode slurry and polymer slurry on the surface of the active layer and curing to obtain a composite layer; In the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a pre-coating layer, and the negative electrode slurry fills the gaps in the pre-coating layer; The coated current collector is pressed into a sheet and immersed in a solvent to dissolve the pre-coating layer and form a groove in the composite layer to obtain a negative electrode sheet.

2. The method for preparing a negative electrode sheet according to claim 1, characterized in that: The step of coating the negative electrode slurry and the polymer slurry on the surface of the active layer and curing to obtain a composite layer comprises: The polymer slurry is coated on the surface of the active layer in a multi-striped coating manner and cured to form the pre-coating layer; Applying negative electrode slurry in the gaps of the pre-coat layer to fill and solidify to obtain the composite layer; or; Coating the negative electrode slurry on the surface of the active layer in a multi-striped coating manner and curing the negative electrode slurry layer; Applying the polymer slurry in the gaps of the negative electrode slurry layer to fill and solidify to obtain the composite layer; or; The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head at the same time and then cured to obtain the composite layer.

3. The method for preparing a negative electrode sheet according to claim 2, characterized in that: The steps of coating the polymer slurry on the surface of the active layer by multi-striped coating and curing to form a pre-coating layer include: Adopt multi-strip coating method, with coating spacing of 0.5mm to 3mm and / or 0.01mm 2 ~0.1mm 2 The polymer slurry is coated on the surface of the active layer and cured to form the pre-coating layer.

4. The method for preparing a negative electrode sheet according to claim 2 or 3, characterized in that: The thickness of the pre-coating layer is 1 / 4 to 3 / 4 of the total thickness of the coating layer of the negative electrode plate.

5. The method for preparing a negative electrode sheet according to claim 4, characterized in that: The polymer used in the polymer slurry is any one of polyamide, polyester and polyether; and the polymer used in the polymer has a molecular weight of 10,000 to 50,000 and / or a melting point of 50° C. to 80° C.

6. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The solvent is any one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, alcohols and benzene.

7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml.

8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The step of pressing the coated current collector into a sheet and immersing it in a solvent to dissolve the pre-coating layer and form a groove on the composite layer to obtain a negative electrode sheet comprises: Roll-pressing the current collector, and then immersing the current collector in the solvent at 40° C. to 50° C. for 1 to 5 minutes to dissolve the pre-coating layer and form a groove on the composite layer; Preferably, after the grooves are formed on the composite layer, the current collector is immersed in N-methylpyrrolidone solvent for 30 to 60 seconds to obtain the negative electrode plate.

9. The method for preparing a negative electrode sheet according to claim 2, characterized in that: The curing method is ultraviolet light curing or drying curing; During the UV curing, the intensity of the UV light is 900 mW / cm 2 ~1100mW / cm 2 , and / or the curing power is 30% to 50%, and / or the curing time is 5 to 15 seconds; During the drying and curing, the current collector is dried in an oven at 40° C. to 50° C.

10. A negative electrode plate, characterized in that: The negative electrode sheet is prepared by the method for preparing the negative electrode sheet according to any one of claims 1 to 9.

11. The negative electrode sheet according to claim 10, characterized in that: In the negative electrode plate, the active material of the negative electrode slurry layer is at least one of graphite, hard carbon, soft carbon, silicon-based materials, titanium-based materials, nitrides, tin compounds, metallic lithium, silicon-doped graphite, and lithium titanate.

12. A lithium ion battery, characterized in that: Contains the negative electrode sheet as claimed in claim 10.